Analisis Penjualan Oli Palsu Menggunakan Merek Oli Ternama pada Kendaraan Bermotor di Wilayah - Alfatah Wilatika; Yani Osmawati (Anomie, 2022)
This study aims to find out what the goals of counterfeit oil product business actors and public workshops are in the Sawangan area of Depok City. The aim of this research is to find out that the expectation of personal gain is high, but it is still subject to situational factors such as police presence, size of loot, and the location of possible crime. The research was designed using qualitative methods which were analyzed using Cornish & Clarke's Rational Choice Theory. This study found the fact that before actual counterfeiting of oil is carried out, the perpetrators must actively decide on counterfeiting the actual brand of oil. This is aimed at business actors making counterfeit oil with the intention of seeking maximum profit and also seeing the risk factors and losses.